DIASTOLIC LEFT VENTRICULAR DYSFUNCTION AND HEART FAILURE WITH PRESERVED EJECTION FRACTION IN ELDERLY - CALENICI Oleg; CARAUȘ Alexandu; MOISEEVA Anna; COCIU Maria; UNTURĂ Ludmila; CARAUȘ Mihaela (Academy of Sciences of Moldova, 2022)
Congestive heart failure with preserved left ventricular systolic function is termed "diastolic heart failure" and is more prevalent in the older population, may account for one half of the older population with congestive heart failure, and may be more common in women than men. The prognosis of patients with congestive heart failure due to diastolic dysfunction is less ominous than in patients with systolic dysfunction yet the morbidity can be high with frequent treatment failures and hospital readmissions.Conclusions: Thus, the diagnosis of heart failure with preserved ejection fraction (HFpEF) on elderly (≥ 85 years old) patients is cumbersome. Diagnosis of heart failure with preserved ejection fraction is challenging in euvolemic patients with dyspnea, and no evidence-based criteria are available. Diastolic LV dysfunction is very common parameter (58 %), but without any specificity for HFpEF, its treatments should be focused on the underlying disease etiology as well as on the derangement in left ventricular diastolic function.